2013
DOI: 10.11634/216796061302370
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intellectual Capital on Jordanian Tourism Sector's Business Performance

Abstract: This study aims at investigating the influence of Intellectual Capital (IC) on Jordanian Tourism (JT) organizations' Business Performance (BP). To approach the aim of the study, practical data were used in the empirical analysis collected from 205 managers (organizations) out of 490 managers (organizations), by means of a questionnaire. Statistical techniques such as descriptive statistics, t-test, ANOVA test, correlation, multiple regressions and stepwise regression were employed. To confirm the suitability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 6 publications
5
26
3
2
Order By: Relevance
“…The findings of this study also support those obtained in the previous studies (e.g. Abdullah & Sofian, 2012;Ahmad, Sharabati, et al, 2013;Martín-de Castro & Delgado-Verde, 2012;Díez et al, 2010, Deep & Narwal, 2014 Vol. 10, No.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The findings of this study also support those obtained in the previous studies (e.g. Abdullah & Sofian, 2012;Ahmad, Sharabati, et al, 2013;Martín-de Castro & Delgado-Verde, 2012;Díez et al, 2010, Deep & Narwal, 2014 Vol. 10, No.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…They claim that, in particular, SC and RC cannot meaningfully exist without HC, and also that HC only creates value through the effective use of SC within an organisation. It is therefore regarded important to consider the integrative nature of IC (van der Meer-Kooistra and Zijlstra, 2001 Kim et al (2012) and Sharabati et al (2013) in the hotel and wider tourism industry, has identified a strong and positive impact and relationship between HC and SC. However, Bontis et al (2000) found a non-significant relationship between HC and SC in the service sector and due to these contradictory results we aim to test this relationship once more in the Jordanian hotel industry.…”
Section: Interrelationships Between Components Of Icmentioning
confidence: 99%
“…Kim et al, 2012, Sharabati et al, 2013. All forms of IC contribute to BP and therefore require attention by hotel managers.…”
Section: Modelmentioning
confidence: 99%
“…In this paper, we use the definition for intellectual capital pushed forward by D. Zegal and consider IC as the sum of all knowledge a company is able to use in the process of conducting business in order to create value [Zegal, 2010]. Currently, there are several points of view on the main components of intellectual capital and their hierarchy: some investigators use the scheme of Skandia Navigator and presuppose that intellectual capital can be subdivided into human and structural capital, which includes innovation and process capital [Edvinsson, 1997;Zegal, 2010;Clarke, 2011], while others identify not only human and structural, but also relational capital as an equally separate component [Sharabatia, 2013;Andreeva, 2016]. The latter point of view is also shared by the business reporting network WICI.…”
Section: Intellectual Capital Structurementioning
confidence: 99%